WACANA PANDEMI COVID-19 TERHADAP PENUTUPAN PERPUSTAKAAN - Muthia Nurhayati (Perpustakaan Nasional RI, 2020)
Coronavirus Disease (COVID-19) has been designated as a pandemic by WHO because of its spread to various countries at the same time. The library did not slip the impact of the COVID-19 pandemic discourse because must be closed as an effort made jointly to break the chain of COVID-19 spread. Through the literature study, especially from scientific journals, the author tries to collect various information related to the closure of library services due to the crisis, in order to find out things that can be done by the library in the midst of a pandemic COVID-19. The study results show that during the COVID-19 pandemic libraries must determine policy related services such as open or not and exemption from fines. It is relevant to consider the disinfectant action against the building and the collection as a whole. The library must be a trusted information center as an effort to slow the spread of viruses and misinformation. Libraries should also provide sources of information that can be accessed by users through electronic resources. Libraries and librarians during the pandemic can be involved as a COVID-19 task force specifically the library building can be used as a logistics warehouse for the distribution of masks, test kits, and personal protective equipment (PPE). Finally, libraries can hold useful programs for users through the concept of